Home self-administration of intravenous antibiotics as part of an outpatient parenteral antibiotic therapy service: a qualitative study of the perspectives of patients who do not self-administer. Issue 1 (25th January 2019) - Tonna, Antonella; Anthony, Geraldine; Tonna, Ivan; Paudyal, Vibhu; Forbes-McKay, Katrina; Laing, Rob; Mackenzie, Alexander; Falconer, Sharon; McCartney, Gillian; Stewart, Derek
Abstract : Objectives: This study aimed to use a theoretical approach to understand the determinants of behaviour in patients not home self-administering intravenous antibiotics. Setting: Outpatient care: included patients were attending an outpatient clinic for intravenous antibiotic administration in the northeast of Scotland. Participants: Patients were included if they had received more than 7 days of intravenous antibiotics and were aged 16 years and over. Twenty potential participants were approached, and all agreed to be interviewed. 13 were male with a mean age of 54 years (SD +17.6). Outcomes: Key behavioural determinants that influenced patients' behaviours relating to self-administration of intravenous antibiotics. Design: Qualitative, semistructured in-depth interviews were undertaken with a purposive sample of patients. An interview schedule, underpinned by the Theoretical Domains Framework (TDF), was developed, reviewed for credibility and piloted. Interviews were audio-recorded and transcribed verbatim. Data were analysed thematically using the TDF as the coding framework. Results: The key behavioural determinants emerging as encouraging patients to self-administer intravenous antibiotics were the perceptions of being sufficiently knowledgeable, skilful and competent and that self-administration afforded the potential to work while administering treatment. The key determinants that impacted their decision not to self-administer were lack of knowledge of available options, a perception that hospital staff are better trained and anxieties of potential complications. Conclusion: Though patients are appreciative of the skills and knowledge of hospital staff, there is also a willingness among patients to home self-administer antibiotics. However, the main barrier emerges to be a perceived lack of knowledge of ways of doing this at home. To overcome this, a number of interventions are suggested based on evidence-based behavioural change techniques.